ANALISA KANDUNGAN BETA-GLUKAN LARUT AIR DAN LARUT ALKALI DARI TUBUH BUAH JAMUR TIRAM (Pleurotus ostreatus) DAN SHIITAKE (Lentinus edodes) - Widyastuti, Netty; baruji, teguh; isnawan, henky; wahyudi, priyo; donowati, donowati (Badan Pengkajian dan Penerapan Teknologi, 2011)
Beta glucan is a polysaccharide compound, generally not soluble inwater and resistant to acid. Beta glucan is used as an immunomodulator (enhancing the immune system) in mammals is usually a beta-glucan soluble in water, easily absorbed and has a low molecular weight. Several example of beta-glucan such as cellulose (β-1 ,4-glucan), lentinan (β-1 0.6-glucan) and (β-1 ,3-glucan), pleuran (β-1, 6 and β-1 ,3-glucan) are isolated from species of fungi Basidiomycota include mushrooms (Pleurotus ostreatus) and shiitake (Lentinus edodes).The purpose of thisresearch activity is to obtain beta-glucan compound that can be dissolved in water and in alkali derived from fungi Basidiomycota, i.e, Oyster mushrooms (Pleurotus ostreatus) and shiitake (Lentinus edodes). The result of beta-glucan compared to characterize the resulting beta glucan that is molecular structure . The difference of beta glucan extraction is based on the differences in solubility of beta-glucan. Beta glucan could be water soluble and insoluble water.